WOMEN AND ISLAM IN THE MEDIEVAL AZERBAIJAN - ALIYEVA, Lala Aghamirze; LATIFOVA , Sevinj (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
Islamisation, changing all spheres of public life in Azerbaijan, did not bypass the gender aspect. In all subsequent periods of the medieval era, the role of women in public and in everyday life was determined by the Islamic Sharia law. In addition, local national traditions also had their own special influence on the status of women. Purpose of the Research. The status of women in medieval societies exhibited both universal patterns and distinct regional variations shaped by religious beliefs and local customs. These historical influences have created enduring cultural models of womanhood that continue to resonate in contemporary societies. In Azerbaijan, the notion of an “ideal Azerbaijani woman” remains a powerful social construct, reflecting centuries of interplay between local traditions and Islamic values. This research examines how the intersection of pre-Islamic Azerbaijani customs and Islamic practices has shaped gender roles and expectations in Azerbaijan, with particular attention to the persistence of these historical influences in modern conceptualizations of feminine identity. By analyzing this cultural synthesis, the study aims at understanding how traditional and religious elements have contributed to current perspectives on gender in Azerbaijani society. Research Methodology. Aiming to study the impact of Islam and dogmas of this religion on the gender issue in the case of Azerbaijan, this article sets the objectives of research both in historical and cultural anthropological perspectives. In this regard, the research benefits from using methods of these fields, alongside Islamic Studies and Gender Studies. Based on an interdisciplinary approach, in this respect the study primarily relies on the comprehensive analysis of the studies by historians, philosophers, and theologians of the medieval period. Moreover, it considers wide-ranging studies from the contemporary period. Scientific Novelty. The role and status of women in Islam have been widely studied from historical and modern perspectives in the case of Middle Eastern countries. This paper is the first attempt to scrutinize this issue in the case of Azerbaijan. And being interdisciplinary, it contributes to various fields of study. Conclusions. The research findings demonstrate that women's roles in medieval Azerbaijan were multifaceted and nuanced, reflecting a complex interplay of Islamic principles, pre-existing cultural traditions, and contemporary socio-political dynamics. The historical synthesis of these influences created distinct patterns of feminine identity and social participation that continue to resonate in modern Azerbaijani society. This historical model of womanhood, characterized by both constraints and spheres of autonomy, remains influential in shaping current cultural expectations and gender norms in Azerbaijan. Keywords: Islam, Women, Gender Issue, Medieval Azerbaijan, Medieval Scholars, Image of Woman.